Formation theory: state and private formations - Briukhovetskyi, Mykola (Actual Problems of Mind, 2020)
In our study, we proceed from the fact that modern social philosophy often refers to the methodological potential of the social formation theory. Certain modifications of the Marxist approach make it possible to use its ideas quite productively for the analysis of modern society. However, it is obvious the formation theory must be cleansed of its ideological meanings and dogmatic forms. In the scientific environment, there is an established tradition of external criticism of the formational approach from the standpoint of others, especially the civilizational one. There is also an internal criticism (critical remarks) of the formation concept, and it aims not at its denial but rather at its improvement. The essential aspects of the internal criticism are the following: the problem of the number of formations and their names, the problem of the status of socialist and communist formations, the issue of formational changing, etc. Our goal is to present such an approach to the understanding of formation theory that is able, at least partially, to overcome some of the enumerated problems, outlined by internal criticism. Thus, we propose a view of formation theory in which all antagonistic formations – slavery, feudalism, and capitalism – have state and private forms. In the state form of the mentioned formations, the state acts as the chief owner and exploiter, represented by the state apparatus. The notion of state slavery and state feudalism allows us to outline within these formations the Asian mode of production as a separate system that cannot be classified. The state form of feudalism allows returning of Kievan Rus’ and the Russian Empire from a "separate" way to the path of the universal historical process. State capitalism makes it possible to reconsider the pages of the so-called socialist history of many countries of the world and finally to unravel the phenomenon of modern China.